Bathyscidius basarai, a new species of the tribe Leptodirini Lacordaire, 1854 (Insecta, Coleoptera, Leiodidae, Cholevinae) from Albania - Čeplík, Dávid; Lakota, Ján; Čeplík, Jaroslav (Zootaxa, 2021)
Bathyscidius basarai D. Čeplík, Lakota & J. Čeplík, sp. nov., is described from Shpella e Blazit cave, located near the village of Bruç in central Albania. The new species is illustrated, morphological comparison with other species, as well as the distribution, including the map for the whole genus Bathyscidius Jeannel, 1910 and information on its natural history is given. The new species is tentatively placed in the subgenus Ionobathyscidius Polak & Jalžić, 2019. Basic zoogeography for the subtribe Bathysiotina Guéorguiev, 1974, with the main focus on taxa of the Balkan Peninsula is provided.